Discourse of economic inequality in Indonesian news media: a sociolinguistic perspective - Ainul Hadziqi (Indonesian Journal of Language and Economic Discourse, 2026)
Background: Economic inequality remains one of Indonesia’s most pressing socio-economic challenges, yet its representation in news media has rarely been examined through a sociolinguistic lens. Objective: The objective of this study is to analyze how Indonesian online news media discursively construct inequality, how linguistic variation reflects social stratification, and how framing strategies shape causal attributions and proposed solutions. Method: Methodologically, this research applies a qualitative design by combining Critical Discourse Analysis, Sociolinguistic Analysis, and Framing Analysis to a purposive corpus of 55 online articles from 2022 to 2024. Results: The results show three key findings: first, news texts tend to legitimize inequality by individualizing poverty and externalizing causes through references to global crises; second, lexical stratification marks elite actors with technical jargon while grassroots voices are reduced to emotive anecdotes; third, framing emphasizes state-centered solutions such as subsidies and welfare while marginalizing community-based alternatives like cooperatives. Implication: The implication of this study is that Indonesian news media not only mirror but also filter public discourse on inequality, privileging elite narratives while limiting democratic deliberation on structural reforms. Novelty: This study uncovers how Indonesian news media linguistically construct and frame economic inequality in ways that legitimize dominant perspectives while constraining alternative narratives of structural change.